MATERIALS FOR FACILITATING EFL LEARNERS IN MAINSTREAM AND CONTENT AREAS - Wuwuh Andayani (JURNAL PENELITIAN PENDIDIKAN BAHASA DAN SASTRA, 2020)
This research is Research and Development (R&D). The steps of this research consisted of the need survey, developing the materials, evaluating the first draft of the materials, revising the first draft, implementing the second draft, and writing the final draft. The instruments of the data collection were questionnaires, an interview guide, and observation guide. The types of the data were quantitative and qualitative. They were analyzed quantitatively and qualitatively. The materials were evaluated and revised based on the data obtained. To respond to that case, therefore, this paper was aimed to investigate the effective and appropriate materials for enhancing EFL learners’ English competency.